Effects of harvest date on apple fruit quality at harvesting and after cold storage - Mohebi, Mina; Babalar, Mesbah; Askari, Mohammad Ali; Talae, Alireza; Ahmadi , Ahmad (Journal of Postharvest Technology, 2017)
The physiochemical changes during the storage in apple fruits (Malus domestica Borkh. cv. Fuji) that were harvested on different dates were studied. Fuji apples were harvested from 9 September till 23 October, at five different times and stored at 0±0.5 °C and 95% humidity for 120 days. To determine the best harvest date for maximum quality and storability, physical and chemical parameters were measured at each harvesting time and after 40-day periods until the end of 120 days of storage. The fruit quality parameters at harvest and after storage, depended on the degree of the ripeness at which the apples were picked. Fruits of the first harvest were firmest before and after storage and had the lowest phenolic compounds at the end of storage. First and third harvest date samples had a decrease in phenolic content and total antioxidant activity in end of storage, but the fourth and fifth harvests fruits showed an increase. Total soluble solids and titrable acidity were affected by the harvest date and storage duration. First and second harvest date samples had increased in total soluble solids during 120 days of storage, but it was decreased in third, fourth and fifth harvested samples. The fifth harvest showed more oblate shape for fruits and plus weight loss in storage duration